2018
DOI: 10.1002/rcm.8246
|View full text |Cite
|
Sign up to set email alerts
|

Production and analysis of multiply charged negative ions by liquid atmospheric pressure matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: Negative ion mode is a sensitive alternative to positive ion mode in liquid AP-MALDI MS analysis. In particular, the analysis of lipids and DNA benefited from the complementarity of the detected lipid species and the vastly greater DNA ion signal intensities in negative ion mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Laser desorption MS and MALDI-MS ion sources operated under vacuum conditions until around 2000 when Laiko et al demonstrated the first AP-MALDI-MS ion source, coupled to an orthogonal time-of-flight (ToF) instrument [3]. Recently, exciting data showing generation of multiply charged species has been demonstrated in ion sources of this form [4,5]. The current state of the art with regards to AP-MALDI-MSI is the high resolution ion source developed by the Spengler group [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Laser desorption MS and MALDI-MS ion sources operated under vacuum conditions until around 2000 when Laiko et al demonstrated the first AP-MALDI-MS ion source, coupled to an orthogonal time-of-flight (ToF) instrument [3]. Recently, exciting data showing generation of multiply charged species has been demonstrated in ion sources of this form [4,5]. The current state of the art with regards to AP-MALDI-MSI is the high resolution ion source developed by the Spengler group [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The neutral liquid MALDI matrix (neutral matrix) consisted of ethylene glycol dissolved in an aqueous ammonium acetate solution (200 mM) in a ratio of 3:5 (v/v), resulting in a pH value of approximately 7. The acidic liquid MALDI matrix (acidic matrix) was DHB dissolved at a concentration of 25 mg/mL in water/acetonitrile/ethylene glycol (3:7:6; v/v/v) with a pH value of approximately 2, which has previously been demonstrated to produce highly protonated protein ions. , Sodium iodide solution was used as provided for calibration of the TOF analyzer in the m / z range of 100–8000 by AP-LDI. A volume of 500 nL of the sodium iodide solution was spotted with 500 nL of ethylene glycol/water (3:5; v/v) and analyzed by ablating material from the droplet edge.…”
Section: Methodsmentioning
confidence: 99%
“…However, multiply charged ions may be produced using an AP ion source and liquid samples . In the case of ultraviolet (UV)-MALDI, the use of typically acidic liquid support matrices (LSMs) produces highly charged ions in the positive ion mode, while basic LSMs are beneficial for producing highly charged ions in the negative ion mode . Proteins as large as apo-transferrin (approximately 80 kDa) have been analyzed in this way .…”
mentioning
confidence: 99%
“…Cramer et al (University of Reading, Reading, UK) showed that, with a retrofitted heated inlet tube on a SYNAPT mass spectrometer (Waters, Wilmslow, UK), negatively multiply charged ions using a liquid matrix can be detected applying several kV difference between the plate and the heated inlet. 83 In collaborative work, Valentine and Li (West Virginia University, Institute, WV, USA) developed a vibrating sharp-edge spray, a voltage-free means of producing liquid droplets just outside a heated inlet tube. 84 Eberlin et al (University of Texas at Austin, Austin, TX, USA) uses a 'MasSpec Pen' for surface analysis using a type of liquid junction in combination with SAI to detect cancerous tissue during surgery.…”
Section: Introductionmentioning
confidence: 99%